The Impact of Covid-19 on Household Welfare in the Comoros : The Experience of a Small Island Developing State - Mendiratta, Vibhuti; Nsababera, Olive Umuhire; Sam, Hannah (Washington, DC: World Bank, 2022)
This paper investigates the causal impact of a Covid-19 lockdown policy on the Comoros's household welfare, poverty, and labor market outcomes. The identification strategy uses the national government lockdown policy implemented to curtail the unexpected outbreak of Covid-19. The lockdown policy coincided with the 2020 Harmonized Survey on Living Conditions of Households data collection, lending itself to a quasi-natural experiment in which households that were interviewed before the lockdown policy fall into the control group, while those that were interviewed after the lockdown fall into the treated group. The paper explores the impact of the Covid-19 using descriptive regression analysis and estimates the causal impact using matching techniques. The analysis finds a reduction in household expenditure, increased poverty, and a reduction in the likelihood of employment. Investigation of differential impacts along the expenditure distribution finds larger impacts at the top of the distribution, suggesting that Covid-19 may have reduced inequality, although the poor were also negatively affected. The evidence also suggests that the ability to use assets as a coping mechanism was limited. In a context of limited safety nets and government interventions, stringent lockdown policies appear to increase the vulnerability of the poor.